2019
DOI: 10.17721/1728_2748.2019.79.37-43
|View full text |Cite
|
Sign up to set email alerts
|

Erechtites hieracifolia (L.) Raf. ex DC. (Asteraceae Bercht. & J. Presl), the new alien species for the Kyiv Polissia

Abstract: Information about floristic record of Erechtites hieracifoliа (L.) Raf. ex DC. (Asteraceae Bercht. & J. Presl) at the territory of the Chernobyl Radiation and Ecological Biosphere Reserve and National Nature Park "Нolosiivsky", new for the Kyiv Polyssia alien species was presented. This species has north american origin, according to the time of arrival it is kenophyte, according to the skidding method – xenophyte, on naturalization level – kolonophyte. Firstly in the region of study this species was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…M. Bieb., and Solidago canadensis L., which are a huge problem in the Polissya region, are almost non-existent in the area (PASHKEVYCH & BURDA, 2017;KOLOMIYCHUK ET AL., 2019;PROTOPOPOVA & SHEVERA, 2019). It should be noted that the first post-pyrogenic stage of dry pine forests is attended by alien species and differs significantly from the classical scheme.…”
Section: Discussionmentioning
confidence: 99%
“…M. Bieb., and Solidago canadensis L., which are a huge problem in the Polissya region, are almost non-existent in the area (PASHKEVYCH & BURDA, 2017;KOLOMIYCHUK ET AL., 2019;PROTOPOPOVA & SHEVERA, 2019). It should be noted that the first post-pyrogenic stage of dry pine forests is attended by alien species and differs significantly from the classical scheme.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the two localities in the Svyatoshyn Forest (within the Svyatoshyn-Bilychi branch of Holosiivskyi National Nature Park) in the western part of the city of Kyiv reported by Kolomiychuk et al (2019), we found rather large colonies of E. hieraciifolius on 2 August 2020 within the city limits of Kyiv in the Pushcha-Vodytsya Forest, in the northwestern part of Kyiv City, north of the city tram station "Spetsdispanser" (coordinates: N 50.526238, E 30.399593, and adjacent areas in the forest compartments 103 and 104 of the Pushcha-Vodytsya Forestry; Fig. 5, B; E2, B).…”
Section: Erechtites Hieraciifolius (L) Raf Ex DC (Asteraceae)mentioning
confidence: 92%
“…62.4 of the ICN: Turland et al, 2018), native to North America and known as naturalized and often invasive in Europe and some other parts of the world (see Belcher, 1956;Cameron, de Lange, 2002;Barkley, 2006;Darbyshire et al, 2012, etc. ), is now actively spreading in western and northern regions of Ukraine (see Orlov, Yakushenko, 2011, Tretyakov et al, 2011Tokaryuk et al, 2017;Kolomiychuk et al, 2019, and references therein), as well as in other countries of Central and Eastern Europe (e.g., Górski et al, 2003;Tretyakov et al, 2011;Bartoszek, 2019;Gudžinskas, Taura, 2020;Zaniewski et al, 2020, etc.). Its invasion in Polissya (the northern forest zone) of Ukraine and adjacent regions of Belarus seems to be especially active at present.…”
Section: Erechtites Hieraciifolius (L) Raf Ex DC (Asteraceae)mentioning
confidence: 99%
“…( Примітка. Хорологічні особливості виду у північній частині Київщини розкриті у декількох публікаціях (Kolomiychuk et al, 2019;Mosyakin, Mosyakin, 2021). Уперше у лісостеповій частині Середнього Придніпров'я колонію цієї потенційно інвазійної чужорідної рослини виявив В.Л.…”
Section: Cymbalaria Muralisunclassified